Improving schools through school choice : an experimental study of deferred acceptance - Klijn, Flip (2019)
In the context of school choice, we experimentally study the student-optimal stable mechanism where subjects take the role of students and schools are passive. Specifically, we study if a school can be better off when it unambiguously improves in the students’ true preferences and its (theoretic) student-optimal stable match remains the same or gets worse. Using firstorder stochastic dominance to evaluate the schools’ distributions over their actual matches, we find that schools’ welfare almost always changes in the same direction as the change of the student-optimal stable matching, i.e., incentives to improve school quality are nearly idle.